Theory Versus Practice in Risk Analysis: An Empirical Study: A Reply. - Greer, Willis R. (The Accounting Review, 1976)
The article presents response of the author on comments made by scholar Peter C. Fishburn on his article "Theory Versus Practice in Risk Analysis: An Empirical Study." Fishburn has provided an excellent mathematical proof of the inconsistency between the von Neumann and Morgenstern expected utility model and the mean-standard deviation model used in my paper. In fact, his point can be made in much more intuitive terms. Also consider two investments with different means, but with the same standard deviations. The impact on g of the risk will be identical for the two investments, again violating the requirement, f < 0. However, I must point out that the general increasing function suggested by Professor Fishburn also violates the f requirement. Notice that Firm 2 chose "R" for investment E and "N" for investment L. Since Fishburn disdosed no inconsistencies between the actual decisions and those made by the general increasing model for Firm 2, the same pair of decisions must have been made by the general increasing model. These decisions call for attaching a larger risk discount to Investment L than to F. Yet L lies strictly above E on the function, so the f, requirement is violated.